Healthcare seeking behaviour among female garment workers in Koggala Free Trade Zone, Sri Lanka - Sanjeeva Rajapakse; Frances Morin; Truls Ostbye; Vijitha De Silva (College of Community Physicians of Sri Lanka, 2018)
Background: In a 2011 study, the prevalence of musculoskeletal disease among a female garment worker group in Koggala Free Trade Zone (Sri Lanka) was estimated to be 15.5%. Nearly all affected women in this group felt their problems disrupted their leisure activities and household work, while only a few reported missing work as direct consequences of their discomfort. The reason why they did not seek treatment or take leave, however, was not clear. Objective: To explore the healthcare seeking behaviour and barriers that prevent female workers at Koggala Free Trade Zone from seeking care Methods: This is an exploratory mixed methods quantitative-qualitative study utilizing pre-interview questionnaires and focus group discussions. Four focus group discussions were held, each consisting of 6 female garment workers (n=24). Discussions were transcribed and processed through three levels of analysis and qualitative coding. Major themes on healthcare seeking and barriers to healthcare were identified using the resulting codebook. Results: The quantitative data showed that more than 90% of focus group participants (n=22) reported musculoskeletal pain in the month prior to the study and less than 30% sought care. Major barriers to healthcare seeking were identified: workers' perception on Western medical treatment and pain, the difficulty in accessing healthcare outside the factory, pressure from management to reach production goals, and financial and personal factors from taking time off work. Conclusions: Multiple factors play a role in healthcare seeking among Sri Lankan female garment workers. Targeted occupational health interventions should focus on alleviating these pain points for garment workers and on educating workers and factory management on the benefits of proactive healthcare seeking behaviour for Sri Lankan female garment workers.